(untitled) (Fiep Bulletin - online, 2014)
Our body lives through a rhythm that produces, it means the life produces rhythm and sound, and consequently that is reflected in our world, in our production. The music, been understood as it goes, it is indeed very important for the child’s development, of the baby, as it is it, of rest, for all of us. The music can calm, relax and transmit to the baby a series of positive references on the half that it surrounds it, giving it the safety’s sensation and good feelings. As well as the music the child’s motive coordination also depends on the physical and mental health, and the music aids in the maturation process. After all it is through the body that the child plays and wins appropriate resources for its sociability, guaranteeing its independence and still contributing so that it has a good concept of itself. The music is also the receiver of a series of cultural references that will reproduce to the listener whenever necessary. In it there are, in a certain way, the roots, the known and family atmosphere, elements that bring comfort, pleasure, relaxation for the mother and consequently for the baby. The human development should be understood as much more than the simple and pure formation of reflexive or associative connections or just the synapses formation.